Adat land laws in Malaysia - Awang, Adibah; Mohd. Ariff, Shahidah (2009)
Adat land is customary land tenure is that it is a matriarchal system or adat pepatih and applicable in the districts of Kuala Pilah, Rembau, Jelebu and Tampin of Negeri Sembilan. In 1909, a Customary Tenure Ordinance was passed and enforced in the four districts above.